2009
DOI: 10.1111/j.1743-6109.2009.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Are the Predictors of Sexual Violence the Same as Those of Nonsexual Violence? A Gender Analysis

Abstract: Introduction Violence manifests itself in such multifarious ways as sexual, physical, and psychological abuse. What has hitherto eluded the medical community, however, is whether sexual and nonsexual abuse share the same predictors. Aim Drawing upon a representative sample of married men and women in the Iranian capital, Tehran, we aimed to determine: (i) the overlap between sexual abuse and physical and psychological violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Indeed, the number of soldiers with founded non-familial major physical violence was smaller during the years of this study (n=5,771) than the number with familial physical violence (15,154), although non-familial sexual violent crime (6,198) was much more common than familial sexual violent crime (718). However, as noted in the introduction, previous research suggests that the predictors of these different types of violent crime vary (Elbogen et al , 2010a, Marshall et al , 2005, Mohammadkhani et al , 2009, Sullivan and Elbogen, 2014), leading us to focus on each of them separately. While the current report presents the results of our model-building efforts to predict non-familial major physical violence, separate reports will have the results of attempts to build comparable models for the other types of violence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the number of soldiers with founded non-familial major physical violence was smaller during the years of this study (n=5,771) than the number with familial physical violence (15,154), although non-familial sexual violent crime (6,198) was much more common than familial sexual violent crime (718). However, as noted in the introduction, previous research suggests that the predictors of these different types of violent crime vary (Elbogen et al , 2010a, Marshall et al , 2005, Mohammadkhani et al , 2009, Sullivan and Elbogen, 2014), leading us to focus on each of them separately. While the current report presents the results of our model-building efforts to predict non-familial major physical violence, separate reports will have the results of attempts to build comparable models for the other types of violence.…”
Section: Methodsmentioning
confidence: 99%
“…The current report presents the results of an attempt to develop a comparable model for violent crime perpetration among U.S. Army soldiers. We focus on non-familial physical violent crimes, excluding family violence and sexual violence , based on evidence that their predictors are different from the predictors of non-familial physical violence (Elbogen et al , 2010a, Marshall et al , 2005, Mohammadkhani et al , 2009, Sullivan and Elbogen, 2014). …”
mentioning
confidence: 99%
“…Sexual coercion is a public health challenge with numerous consequences [1], [2] and predisposing factors [3]. Experiences of sexual coercion tend to be under-reported, although the consequences for its victims remain [4].…”
Section: Introductionmentioning
confidence: 99%
“…15 Findings are mixed about whether one type of violence precedes or predicts the other. Mohammadkhani et al, 16 for instance, found that the experience of physical or psychological violence increased the likelihood of sexual violence victimization. Trickett et al, 17 on the other hand, found that sexual abuse predicted later victimization with physical or further sexual violence.…”
Section: Introductionmentioning
confidence: 99%